ANALISIS KOMPARATIF PENDAPATAN USAHATANI PADI SAWAH SISTEM TABELA DAN TAPIN DI DESA TINDAKI KECAMATAN PARIGI SELATAN KABUPATEN PARIGI MOUTONG - Ardiansya Ardiansya; Sulaeman Sulaeman; Moh Alfit A. Laihi (AGROTEKBIS : JURNAL ILMU PERTANIAN (e-journal), 2022)
The research was conducted in Tindaki village, South Parigi sub district, Parigi Moutong district, in April to June 2021. The study aimed to compare the income of lowland rice farmers using two different system, the direct planting system (DPS) and the transplantation system (TS). The study used the proportional stratified random sampling technique to select 38 farmer respondents from 300 lowland rice farmers, consisting of 156 farmers who use the DPS and 144 farmers who use the TS. The hypothesis testing was carried out using test-1 of two independent sample separated variance. The research location was chosen purposively with consideration that Tindaki is one of the rices producing villages that uses the DPS and The TS in South Parigi district of Parigi Moutong district. The results of the study showed that the income of the rice farmers using the DPS was significantly higher compared to the income of the farmers using the TS. Specifically, the income of the DPS rice farmers was IDR. 13,969,608.33 ha/planting season (PS), while the income of the TS rice farmers was IDR 10,315,005.04 ha/PS. The study obtained a t-count value of 0.24, with a 5% t-table of 2.03. Since the t-count was smaller that the t-table value, the null hypothesis (H0) was accepted. This indicates that the income of the lowland rice farmers using the DPS is not significantly different from their counterpart income in Tindaki village, South Parigi sub district, Parigi Moutong district.